EMPOWERING YOUNG LEARNERS' VOCABULARY OF TOURISM THROUGH FLASH CARDS IN AMBARITA VILLAGE, KEC. SIMANINDO, DISTRICT SAMOSIR - Rahmat Huda; Parapat, Lili Herawati; Sholidha Ramadiah Harahap, Siti Aisyah, Novyola Cindy Aprina, Annisah Fitri Andani (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this community service is to increase understanding and mastery of tourism vocabulary among children in Ambarita Village, Simanindo District, Samosir Regency, which has rich tourism potential. Even though this village is known for its rich Batak culture and historical tourist attractions, many children in the village are less familiar with vocabulary related to tourism. For this reason, this service activity implements the use of flashcards as a learning medium to introduce and strengthen tourism vocabulary. This activity involves elementary school age children who are trained in recognizing and mastering terms related to local tourism. The results of this activity show that the use of flashcards can significantly improve children's language skills in a tourism context. Apart from that, this activity also succeeded in increasing children's interest in the world of tourism and gave them a deeper understanding of the importance of this sector in regional development. This service not only has a positive impact in developing children's language skills, but also contributes to strengthening their awareness of the tourism potential around them.